2016
DOI: 10.15376/biores.11.4.9290-9301
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Beating of Bacterial Cellulose and their Influence on Paper Properties

Abstract: Three dispersion instruments (a standard laboratory disintegrator, PFI beater, and ultrasonic cell disrupter) were tested to determine their effects on the dispersion of bacterial cellulose (BC) wet films. After treatment with a standard 10000 r disintegrator treatment, there was still a large number of undispersed fiber bundles in the BC suspension. The BC films were dispersed well after PFI beating revolution at 30000 r, and the cationic charge demand of the BC suspension reached 2.4 × 10 -4 eq·g -1 . The ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In our case, the increase of the BC cationic demand could be performed without adding reagents by raising the surface area in contact with water. Addressing this matter, a study developed by Yuan et al demonstrated that a sharp increase in the cationic demand is obtained by just disintegrating the membranes, reaching its maximum after beating suspensions with 10% of BC material at 8000 rpm [ 56 ]. This treatment after the membrane synthesis could provide an enhancement of the performance when treating waters with low metal content.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, the increase of the BC cationic demand could be performed without adding reagents by raising the surface area in contact with water. Addressing this matter, a study developed by Yuan et al demonstrated that a sharp increase in the cationic demand is obtained by just disintegrating the membranes, reaching its maximum after beating suspensions with 10% of BC material at 8000 rpm [ 56 ]. This treatment after the membrane synthesis could provide an enhancement of the performance when treating waters with low metal content.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this result may have been related to the aggregation of the bacterial cellulose resulting in the index of tear strength being reduced. The accumulation of bacterial cellulose fibers was inversely related to the strength of the sheets [46,47]. It was also found that increasing the amount of nata de coco changed the water absorption properties of the bacterial cellulose sheets as the sheets became more water-resistant.…”
Section: Physical Properties Of Bacterial Cellulose Filtermentioning
confidence: 92%
“…D. Johnson et al [ 170 ] proposed improving the tensile properties of paper by using a BC additive. Xiang et al [ 167 ] and Yuan et al [ 171 ] also announced that a homogeneous dispersion of BC within the paper matrix is an important factor to manufacture successfully reinforcing paper. To succeed in this process, intense stirring [ 172 , 173 ] or acid hydrolysis [ 34 ] was tried, but the homogeneous dispersal was difficult due to the high entanglement of the nanofibers reached during culture [ 172 ].…”
Section: Applicationsmentioning
confidence: 99%